Statistical analysis of the relationship between temperature and amount of evaporation in Erbil and Sulaymaniyah provinces : between the years (2013-2021) - Hawre Peshraw Tawfeeq (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The aim of this study is to show the relationship between temperature and evaporation in both Erbil and Sulaimani provinces between 2013-2021, to show this relationship, after analyzing both temperature and evaporation, through the Person correlation coefficient in (SPSS) analysis Statistics have been done for the relationship between them. For this purpose, our research plan on the first topic: analysis of the elements of temperature and evaporation, Topic 2: Statistical analysis of the relationship between temperature and evaporation. The results showed that temperature and evaporation varied according to years and stations, which affected the relationship between the two variables. This relationship was direct in some stations and inverse in others.